2010
DOI: 10.1007/s13277-010-0128-3
|View full text |Cite
|
Sign up to set email alerts
|

NSSR1 is regulated by testosterone in the mouse uterus and extensively expressed in endometrial carcinoma

Abstract: Neural salient serine/arginine-rich protein 1 (NSSR1) has been found to play important roles in inhibiting alternative splicing during heat shock and mitosis and is predominantly expressed in neural tissues such as cerebral neurons, cerebellar Purkinje cells and bipolar cells of the retina. Recently, NSSR1 has also been shown to be highly expressed in the testes, suggesting its potential roles in reproductive system. In this report, the expression of NSSR1 in the columnar epithelium of the endometrium and glan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…In addition, recently we have reported that NSSR1 is also highly expressed in reproductive system, indicating the potential roles NSSR1 may play in reproduction [18]. In mouse female reproductive system, we found that NSSR1 is developmentally expressed in the uterus and extensively distributed in endometrial carcinoma [19]. In male reproductive system, our results showed that the expression of testicular NSSR1 increased significantly during mouse testes development and NSSR1 was mainly expressed in germ cells, but barely detected in sertoli cells.…”
Section: Introductionsupporting
confidence: 52%
“…In addition, recently we have reported that NSSR1 is also highly expressed in reproductive system, indicating the potential roles NSSR1 may play in reproduction [18]. In mouse female reproductive system, we found that NSSR1 is developmentally expressed in the uterus and extensively distributed in endometrial carcinoma [19]. In male reproductive system, our results showed that the expression of testicular NSSR1 increased significantly during mouse testes development and NSSR1 was mainly expressed in germ cells, but barely detected in sertoli cells.…”
Section: Introductionsupporting
confidence: 52%
“…Previous studies have shown that SRSF10 is upregulated in colorectal cancer as a key regulator of BCLAF1 pre-mRNA splicing and thus maintaining the oncogenic phenotype of colon cancer cells [ 36 , 37 ]. In addition, the expression and distribution of SRSF10 are developmentally and hormonally regulated and increased in endometrial carcinomas as well as ovarian cancers, supporting its potential involvement in uterine development and tumorigenesis [ 38 ]. Here, our study infered the oncogenic role of SRSF10.…”
Section: Discussionmentioning
confidence: 99%